Pharmacoinvasive strategy in the treatment of acute myocardial infarction: current state-of-the-art - A. S. Tereshchenko; T. M. Uskach; N. V. Kondratova (Российский кардиологический журнал, 2021)
The existing clinical guidelines identify two main approaches to the treatment of patients with ST-segment elevation myocardial infarction: a primary percutaneous coronary intervention and a pharmacoinvasive strategy. Due to the time delays due to various reasons, it is not always easy to perform primary percutaneous coronary intervention timely (<120 minutes). Modern thrombolytic drugs make it easy and safe to apply a pharmacoinvasive strategy to a wide group of patients, improving their prognosis.